2017
DOI: 10.1002/ece3.2957
|View full text |Cite
|
Sign up to set email alerts
|

Spatial overlap of shark nursery areas and the salmon farming industry influences the trophic ecology of Squalus acanthias on the southern coast of Chile

Abstract: Potential interactions between marine predators and humans arise in the southern coast of Chile where predator feeding and reproduction sites overlap with fisheries and aquaculture. Here, we assess the potential effects of intensive salmon aquaculture on food habits, growth, and reproduction of a common predator, the spiny dogfish—identified as Squalus acanthias via genetic barcoding. A total of 102 (89 females and 13 males) individuals were collected during winter and summer of 2013–2014 from the Chiloé Sea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Despite differences in the trophic patterns of S. acanthias due to the spatial association with intensive salmon farming, there appeared to be no difference in fecundity or size at maturity compared to other populations (Gaitán‐Espitia et al . ).…”
Section: Salmon Farming Environmental Impacts During the Marine Fattementioning
confidence: 97%
See 1 more Smart Citation
“…Despite differences in the trophic patterns of S. acanthias due to the spatial association with intensive salmon farming, there appeared to be no difference in fecundity or size at maturity compared to other populations (Gaitán‐Espitia et al . ).…”
Section: Salmon Farming Environmental Impacts During the Marine Fattementioning
confidence: 97%
“…Gaitán‐Espitia et al . () studied the interaction between the piked dogfish Squalus acanthias and salmon farms in Patagonian fjords. They found that the spatial overlap of shark nursery areas and the salmon industry influences the trophic niche of S. acanthias in this region by adding new food items (i.e.…”
Section: Salmon Farming Environmental Impacts During the Marine Fattementioning
confidence: 99%
“…Although many aquafeeds are most commonly composed of fishmeal and fish oil, many manufacturers are moving to more sustainable plant‐based ingredients, which modify the fatty acid composition and fat content levels of tissues of wild fish that feed on the lost pellets 6,304 . In addition, antibiotics in some feeds have the potential to accumulate in the tissues of the wild fish and result in liver damage, acute toxic effects, bacterial resistance, and immune system suppression 298 …”
Section: Protected Species and Marine Aquaculturementioning
confidence: 99%
“…Benthic macro‐invertebrate communities can change in the presence of aquaculture farms because of crop and biofouling organism drop‐off and the deposition of farmed fish faeces and uneaten food pellets 56,305–308 . If preferred prey items are not available, sharks may be forced to alter their diets and scavenge dead fish accumulating in cages and uneaten feed beneath farms 289,290,298 . Depending on the shark species and their foraging habits, these farm‐induced dietary changes raise concern about the potential effect of farms on the biology of these predators, their trophic interactions, and ecosystem function at different spatial and temporal scales.…”
Section: Protected Species and Marine Aquaculturementioning
confidence: 99%
“…Coastal development, pollution, dredging, and bottom trawling affect coastal or demersal habitat that the species' prey relies on (ASMFC 2002). In Chile, spatial overlap of nursery areas and aquaculture farms have been identified; the effect of this interaction appears to influence the diet of the Spiny Dogfish, but any effect on the species' reproductive output is unknown (Gaitán-Espitia et al 2017).…”
Section: Threats (See Appendix For Additional Information)mentioning
confidence: 99%